Understanding the Sources of Online Travel Information. (January 2018) - Choi, Youngjoon; Hickerson, Benjamin; Kerstetter, Deborah
Given that online travel media enable multilateral communication patterns in destination marketing, this study investigates technical attributes presenting the number and type of source-related visual cues. From a technological perspective, the sources of online travel information can be conceptualized in terms of specialization, endorsement, and other users' star rating to reflect technological functions and psychological effects. An experiment with a 2 (specialization: a generalist website vs. a specialist website) × 2 (endorsement: absence vs. presence) × 3 (star rating: low vs. medium vs. high) factorial between-subjects design was conducted to test the relationships between source-related visual cues, cue-induced perceptions, information credibility, and destination images. This study found that each source-related visual cue produced distinctive psychological effects on a tourist's perceptions. Furthermore, these cue-induced perceptions were influential to tourists' judgment of information credibility, which was positively related to destination images and behavioral intention.